2003
DOI: 10.1523/jneurosci.23-04-01383.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Photoreceptors and Cone Bipolar Cells in the Developing and Mature Retina

Abstract: An antibody against recoverin, the calcium-binding protein, labels photoreceptors, cone bipolar cells, and a subpopulation of cells in the ganglion cell layer. In the present study, we sought to establish the origin and identity of the cells expressing recoverin in the ganglion cell layer of the rat retina. By double labeling with rhodopsin, we demonstrate that early in development some of the recoverin-positive cells in the ganglion cell layer are photoreceptors. During the first postnatal week, these rhodops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…The presence of ectopic S-opsin cells in the INL of rd7 and Nrl −/− retinas is reminiscent of previous findings showing opsin-like immunoreactive cells in the developing retina [25]. Our study reveals the presence of ectopic S-opsin positive cells that persist and survive in the adult retinas from Nrl −/− and rd7 mice.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of ectopic S-opsin cells in the INL of rd7 and Nrl −/− retinas is reminiscent of previous findings showing opsin-like immunoreactive cells in the developing retina [25]. Our study reveals the presence of ectopic S-opsin positive cells that persist and survive in the adult retinas from Nrl −/− and rd7 mice.…”
Section: Discussionsupporting
confidence: 89%
“…Opsin-like-ir cells that express several phenotypic characteristics of rods have previously been noted in the INL of the developing rat retina (Barnstable, 1982;Araki et al, 1988). More recently, a few rhodopsin-positive profiles were observed in both the INL and the prospective GCL of developing rats (Gü nhan- Agar et al, 2000;Gü nhan et al, 2003). As in sharks (present results), ectopic rod opsin expression in the rat is transient.…”
Section: Ectopic Opsin-immunoreactive Cells In the Inl Of Elasmobranchssupporting
confidence: 80%
“…It has been suggested that these cells may either degenerate or undergo phenotypic conversion during subsequent maturation of the retina (Araki et al, 1988). Indeed, these opsin-like cells were interpreted as a contingent of photoreceptors that fail to recognize a signal to stop migrating when they arrive at the photoreceptor layer, and that their early elimination from the GCL and later from the INL probably reflects the failure of these cells to form functional synapses in inappropriate retinal layers (Gü nhan et al, 2003).…”
Section: Ectopic Opsin-immunoreactive Cells In the Inl Of Elasmobranchsmentioning
confidence: 99%
“…Rhodopsin is a photopigment found in rods, the most common type of photoreceptor in the retina. 34 Bipolar cells were identified by Protein Kinase C (PKC) alfa. [34][35][36] Different subpopulations of amacrine cells were identified by calcium binding proteins: calbindin, calretinin, and parvalbumin.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…34 Bipolar cells were identified by Protein Kinase C (PKC) alfa. [34][35][36] Different subpopulations of amacrine cells were identified by calcium binding proteins: calbindin, calretinin, and parvalbumin. [37][38][39][40] The same proteins may also be present in ganglion cells; however, a more specific marker of ganglion cells was used, Brn3a.…”
Section: Immunocytochemistrymentioning
confidence: 99%